Sustainability of U.S. Soybean Production: Conventional, Transgenic, and Organic Production Systems - Heatherly, Larry; Dorrance, Anne; Hoeft, Robert; Onstad, David; Orf, James; Porter, Paul; Spurlock, Stan; Young, Bryan (Council for Agricultural Science and Technology (CAST), 2009)
This CAST Special Publication documents the ecological and economic implications of the various systems used in U.S. soybean production. Soybean production has changed in the United States since its first introduction in the mid-1880s. Initially, the crop was produced mainly for forage and received only minimal inputs. Today, soybeans have become a major source of protein in animal diets and vegetable oils for human consumption. Considering this dramatic change, CAST is providing a comprehensive literature review that evaluates U.S. soybean production systems currently in use with respect to their environmental and economic sustainability.